Methanogenesis stimulation and inhibition for the production of different target electrobiofuels in microbial electrolysis cells through an on-demand control strategy using the coenzyme M and 2-bromoethanesulfonate. (October 2019) - Park, Sung-Gwan; Rhee, Chaeyoung; Shin, Seung Gu; Shin, Juhee; Mohamed, Hend Omar; Choi, Yun-Jeong; Chae, Kyu-Jung
Abstract: Electron allocation through the suppression or the stimulation of methanogenesis is critical for microbial electrolysis cells (MECs) to produce the desired target product (e.g., CH4 or H2 ). In this study, selective methanogenesis control using the coenzyme M (CoM) and 2-bromoethanesulfonate (2-BES) was investigated in a two-chambered MEC to evaluate the effect of CoM and 2-BES on the production of different electrobiofuels, net energy conversion efficiency and microbial community structure. Because the CoM is a crucial methyl-group carrier in the final process of methanogenesis, it was postulated that CoM would stimulate methanogenic activity at the anode, while a structural analog of the CoM (i.e., 2-BES) was expected to improve cathodic H2 yield using electrons conserved because of methanogen inhibition (electron equivalence: 8 mol e −  = 1 mol CH4  = 4 mol H2 ). CoM injection in MECs significantly enhanced their CH4 production rate, purity, and yield by 4.5-fold, 14.5%, and 76.1%, respectively, compared to the control. Moreover, microbial community analysis indicated that Methanosaeta, the major acetoclastic methanogen, continued to dominate the microbial community but steadily decreased in relative abundance after the CoM injection. On the other hand, drastic increases in hydrogenotrophic methanogens, such as Methanoculleus and Methanolinea, were observed along with potential syntrophic acetate-oxidizing bacteria. In contrast, CH4 production in the 2-BES injected trials was significantly inhibited by 79.5%, resulting in a corresponding increase of H2 production by 145.5% compared to the control. Unlike the CoM, the microbial community did not noticeably change when 2-BES was injected, although the population size gradually decreased over time. Also, a single injection of CoM and 2-BES, even at low concentrations (500 μM), enabled the desired allocation of electrons as characterized by a high sensitivity, fast response, and negligible interference. In terms of energy conversion efficiency, methanogenesis stimulation approach resulted in higher net energy production than inhibition approach, whereas the remained electrons were not fully converted to hydrogen in case of the inhibition trial, thus producing less energy. Graphical abstract: Unlabelled Image Highlights: Selective methanogenesis control method for electrobiofuel production was developed. Coenzyme M (CoM), a methyl-group carrier, was used as a methanogenesis stimulator. 2-bromoethanesulfonate (2-BES), a structural analog of CoM, inhibited methanogenesis. CoM increased CH4 production through activation of methanogens and potential SAOBs. 2-BES increased H2 production using electrons conserved by CH4 production inhibition.